2017
DOI: 10.1177/1747954117711866
|View full text |Cite
|
Sign up to set email alerts
|

The effect of technique on tackle gainline success outcomes in elite level rugby union

Abstract: Tackling is a major component of rugby union and effective attacking and defensive play are essential for game outcomes. In this study, a number of pre-contact, contact and post-contact tackle characteristics that had an influence on tackle gainline success for the ball carrier and tackler were identified using match video evidence from European Rugby Champions Cup games. A total of 122 front-on tackles and 111 side-on tackles were analysed. For each ball carrier and tackler characteristic, the Odds Ratio and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 19 publications
(57 reference statements)
3
50
0
Order By: Relevance
“…Previous studies have shown that fending has a positive effect on ball carrier tackle outcomes Tierney et al, 2018c;Wheeler & Sayers, 2009). One study found that a moderate fend increased the chance of offloading whilst another study reported that a strong fend compromised the quality of the tackler's positioning (Wheeler & Sayers, 2009).…”
Section: Generalmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have shown that fending has a positive effect on ball carrier tackle outcomes Tierney et al, 2018c;Wheeler & Sayers, 2009). One study found that a moderate fend increased the chance of offloading whilst another study reported that a strong fend compromised the quality of the tackler's positioning (Wheeler & Sayers, 2009).…”
Section: Generalmentioning
confidence: 98%
“…In one season alone, one study found that 23% of elite level Rugby Union participants suffered a concussion (Shuttleworth-Edwards et al, 2008). It is well understood that both correct tackler and ball carrier technique are necessary for successful and safe participation in rugby union (Hendricks & Lambert, 2010Tierney, Denvir, Farrell, & Simms, 2018a, 2018cTierney, Krosshaug, Wilson, & Simms, 2015), and that incorrect tackle technique is a risk factor for injury Hendricks et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…3 Tackling is regarded as the most common cause of injury and concussion in rugby union. 4,5 Correct technique in the tackle is essential for safe and successful tackle outcomes, [6][7][8] whilst poor tackle technique is a reported risk factor for injury 9,10 and direct head impact causation. 2,11 This indicates the importance for concussion injury prevention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The linear and angular velocity values for each time frame can be seen in Appendix A. Although it was a side-on tackle, 24 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r…”
Section: Resultsmentioning
confidence: 99%